Efforts to Improve the Competitiveness of Chicken Egg Sales - Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
In this research, the background is that there is a lot of competition between entrepreneurs, especially in attracting consumer interest in products so that they can increase their business competitiveness. One way is to implement a marketing strategy. The marketing strategy must be structured effectively in order to be able to create the right strategy as a top priority in the business being carried out in order to maintain the company's existence. The focus of this research is to find out the implementation of the marketing strategy for the Chicken Egg Business in Kuncen Hamlet in increasing the competitiveness of SMEs, to find out the obstacles encountered in implementing the marketing strategy for the Chicken Egg Business in Kuncen Hamlet in increasing the competitiveness of SMEs. The type of research used is descriptive research using a qualitative approach. The method used in data collection is the method of interviews, observations, and documentation. The results of the research show that the marketing strategy used by the Chicken Egg Business is to segment the market, target market, market position, and marketing mix; there are obstacles that affect the marketing strategy in the Chicken Egg Business; The marketing strategy carried out by the Chicken Egg Business has been quite effective in terms of increasing production and sales from year to year.